2018
DOI: 10.3389/fnins.2018.00216
|View full text |Cite
|
Sign up to set email alerts
|

Indole, a Signaling Molecule Produced by the Gut Microbiota, Negatively Impacts Emotional Behaviors in Rats

Abstract: Gut microbiota produces a wide and diverse array of metabolites that are an integral part of the host metabolome. The emergence of the gut microbiome-brain axis concept has prompted investigations on the role of gut microbiota dysbioses in the pathophysiology of brain diseases. Specifically, the search for microbe-related metabolomic signatures in human patients and animal models of psychiatric disorders has pointed out the importance of the microbial metabolism of aromatic amino acids. Here, we investigated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
186
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(189 citation statements)
references
References 63 publications
3
186
0
Order By: Relevance
“…The current data point to a strong link between intestinal inflammation, disruption of serotonin signaling and the consequent alteration in gut motility, and development of depression. Presently, there were some studies, which implied another mechanism by the creation of the neuro‐suppressive indole‐derivatives; alternative probable mechanism might be through stimulation of the vagal afferent fibers . Overall, additional studies are necessary for a complete understanding of the interaction of this bacterial organism and depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current data point to a strong link between intestinal inflammation, disruption of serotonin signaling and the consequent alteration in gut motility, and development of depression. Presently, there were some studies, which implied another mechanism by the creation of the neuro‐suppressive indole‐derivatives; alternative probable mechanism might be through stimulation of the vagal afferent fibers . Overall, additional studies are necessary for a complete understanding of the interaction of this bacterial organism and depression.…”
Section: Discussionmentioning
confidence: 99%
“…[50][51][52][53] There have been various preceding studies with focus on the effects of the "microbiota-gut-brain axis". 54,55 To search the role of Figure 7). The result suggested that frontal Cortex 5-HT exhibited negative associations with the ratio of Firmicutes in total gut microbiota, which suggested there might be a negative feedback mechanism between gut microbiota and neurotransmitter.…”
Section: Discussionmentioning
confidence: 99%
“…, which is unable to produce indole, only rats colonized with wild-type strain showed anxiety-like behavior suggesting that indole and its metabolites might play a role in developing depression [136]. This study implies a direct mechanism by which the gut microbiota can influence the brain, and result in a state of depression, in this case via the production of the neurosuppressive indole-derivatives; oxindole and isatin, which are products of gut epithelial or hepatic xenobiotic metabolizing enzymes ( Figure 1D).…”
Section: The Dual Effect Of Gut Microbiota and Its Metabolites In Depmentioning
confidence: 99%
“…Some metabolites are closely linked with neurological disorders, either to positive or negative outcomes (92,93). Several examples have been reported of gut metabolites entering circulation and directly affecting the brain, as well as cases where metabolites stimulate pathways in the gut, immune, or autonomic nervous system and exert changes to the brain and to behavior (94)(95)(96)(97). Comprehensive metabolic profiling in humans and animal models provides insight into the molecular status of disease and how genetic factors and environmental risks interact.…”
Section: Discussionmentioning
confidence: 99%